Work Family Conflict and Organizational Commitment Impact on Job Satisfaction - Sijabat, Asiani; Hiariey, Harvey; Siahainenia, Selfiena; Pelupessy, Merry M; Tehuayo, Erlinda (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The aim of this research is to see the extent of the influence of Work Family Conflict and organizational commitment on performance. The research object is BCA Ambon Branch.The population in this study were employees at BCA Bank Ambon Branch, with the population and sample used in this study being the Saturated Sample where the entire population was sampled, namely 43 employees. The analytical tool used is Multiple Linear Regression Analysis. The research results prove thatWork-Family Conflictsignificant positive effect on job satisfaction, and organizational commitment has a significant positive effect on job satisfaction.